أثر استخدام أسلوب العصف الذهني في تعلم بعض الألعاب في درس التربية الرياضية - الفرطوسى، عبد على عبيد (الأكاديمية الدولية لتكنولوجيا الرياضة, 2020)
يهدف البحث إلى: تطبيق طريقة العصف الذهني في درس التربية الرياضية للمرحلة المتوسطة وافترض الباحث وجود فروق ذو دلالة إحصائية بين مستوى تعلم المهارات الأساسية في درس التربية الرياضية للطلبة الذين يدرسون بأسلوب العصف الذهني، والطلبة الذين يدرسون بالأسلوب التقليدي في درس التربية الرياضية وتمثل مجتمع البحث من طلاب الصف الثاني متوسط بـ (187) طالبا واعتمد الباحث المنهج التجريبي لملائمته مع متطلبات البحث الحالي ولتحقيق ذلك اعتمد تصميم المجموعتين التجريبية والضابطة، كما قام الباحث بتطبيق التجربة وفق الضوابط التامة التي تطرق لها في الإطار النظري حول آلية تنفيذ جلسة العصف الذهني وتم الاعتماد على الاختبار العملي الذي ويشتمل الاختبار بصورته النهائية على (30) اختبار أعطيت درجة واحدة للأداء الصحيح وصفر للأداء الخاطئ وتم إجراء التجربة الاستطلاعية على عينة مكونة من (8) طلاب وتم استخراج الأسس العلمية للاختبارات وتضمن البرنامج التعليمي (8) وحدة تدريسية بحسب الدروس المخصصة للتربية الرياضية موزعة على المجموعتين التجريبية والضابطة بواقع (4) وحدة تدريسية لكل طريقة وقد استغرقت التجربة الفعلية (4) أسابيع وزعت خلالها الوحدات وبواقع وحدتين تعليميتين في الأسبوع لكل مجموعة وكان زمن الوحدة التعليمية الواحدة (40) دقيقة. وتم تطبيق وحدات البرنامج التعليمي على مجموعة البحث التجريبية بعد انتهاء الباحث من تطبيق البرنامج التعليمي وتطبيق درس التربية الرياضية بطريقة العصف الذهني واستخدام الباحث الوسائل الإحصائية الآتية في معالجة البيانات من الحقيبة الإحصائية (spss). وبعد عرض ومناقشة النتائج تم التوصل إلى الاستنتاجات: 1-فاعلية استخدام طريقتي العصف الذهني والمحاضرة في درس التربية الرياضية. 2-تفوق أفراد المجموعة التجريبية التي درست وفق طريقة العصف الذهني على أفراد المجموعة الضابطة التي درست بالطريقة التقليدية. The research aims to: Application of the method of brainstorming in the lesson of physical education for the intermediate stage The researcher hypothesized that there are statistically significant differences between the level of learning the basic skills in the lesson of physical education for students who study in the method of brainstorming, and students who study in the traditional way in the lesson of physical education and represent the research community of second grade students average (187) students. The researcher adopted the experimental method to suit the current research requirements. To achieve this, the design of the experimental and control groups was adopted. The researcher applied the experiment according to the complete controls that were discussed in the theoretical framework on the mechanism of implementing c (30) tests were given one degree for the correct performance and zero for the wrong performance. The pilot experiment was conducted on a sample of (8) students. The scientific basis of the tests was extracted and the educational program included (8) (4) teaching units for each method. The actual experiment lasted 4 weeks, during which the units were divided by two teaching units per week for each group. The time of the unit was 40 minutes. The units of the educational program were applied to the experimental research group after the researcher completed the application of the educational program and the application of the lesson of physical education in a brainstorming method. The researcher used the following statistical methods in processing data from the statistical file (spss) After discussing and discussing the results, the conclusions were reached: 1- The effectiveness of the use of the methods of brainstorming and lecture in the lesson of physical education 2- The members of the experimental group, which was studied according to the method of brainstorming on the members of the control group studied in the traditional way.
Keywords: الأساليب التعليمية -- التربية الرياضية -- المجالات الرياضية